Evaluation of candidate reference genes for gene expression research in Vespula vulgaris - McLaughlin, Gemma M. (Frontiers in Insect Science, 2025)
IntroductionVespula vulgaris is an invasive wasp that causes considerable detriment to native birds and invertebrates in New Zealand. Reducing at least 80% of invasive wasp densities is necessary to manage the problems this species presents to its invaded range. To explore the function of target genes for the genetic management of V. vulgaris, screening of appropriate reference genes is crucial for conducting the reverse transcriptase-quantitative real-time PCR (RT-qPCR). The selection of appropriate reference genes is an important but often overlooked consideration when delving into RNA research. Many studies rely on one of two tried and trusted reference genes widely used in the literature, which may not be suitable for the normalization of data under particular variables.MethodsHere, I selected six reference genes of V. vulgaris and evaluated their stability across two conditions: developmental stage and sex by using five different tools for analysis: the ΔCt method, geNorm, NormFinder, BestKeeper, and RefFinder.ResultsDiffering appropriate reference genes for different research foci: TBP, EF1A, RPL18X3, and CAPZB for developmental stage treatment, and KTB, EF1A, and CAPZB amongst the sexes.DiscussionMy study further emphasizes that there is no “one size fits all” reference gene, and advocates for analysis of reference gene suitability when conducting gene quantification experiments.